Optimization of low normal force contact spring - Bhuiyan, Moinul (2009)
Enable the design of a small contact spring for applications requiring high density, high speed and high durability. A low normal force contact spring with high performance is fabricated using a unique combined technology (photo resist lithography and electro fine forming technology). To determine an appropriate hertz stress by several radius contact R (5-200μm) with low normal force (0.10N-0.16N at 0.45mm) is designed. For a reliable contact spring, NiCo material is selected because its material characteristics are better than commercial contact spring material. By the experiment, it is proved that a low normal force spring with higher hertz stresses which is 5μm radius can provide a stable reliable contact resistance from the first contact than 200μm radius. The evaluated results by the experiment currently proved the durability of 0.30 million contact cycles (less than 50m.) without any difficulty. In this research, we focused to investigate an appropriate Hertz stress, which will be utilize in future design concept for miniature size contact spring. We think this method will be very important to decrease a total material cost in connector business field.